Cross-linguistic Influence in the Syntactic Domain in Simultaneous Language Acquisition: Evidence from Extraction Constructions Involving the Object of a Preposition in the Speech of an English-Spanish Bilingual Child. - Vásquez Carranza, Luz Marina (2012)
This study reports evidence of cross-linguistic influence in the speech of an English-Spanish simultaneous bilingual child between ages 2;3 and 5;6. in extraction constructions involving the object of a preposition (i.e., pied-piping and preposition stranding). Relevant data by 11 English monolingual children revealed no instances of pied-piping constructions despite the fact that these are grammatical in adult English speech; in contrast, 46% of the relevant constructions in the bilingual child's speech contained pied-piping. Similarly, whereas the data by 14 Spanish monolingual children never evidenced preposition stranding, which is never a grammatical option in Spanish, the bilingual child data did so in 26% of his relevant constructions. These qualitative differences between the monolingual and the bilingual child data strongly suggest cross-linguistic influence.